Leader-follower model of reciprocal FDI and international trade - Cieślik, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
In this paper we develop a two-country leader-follower model of reciprocal horizontal foreign direct investment (FDI) and international trade. First, we identify the conditions necessary for exporting and FDI depending on trade costs and the cost of foreign investment. Then, we demonstrate how various types of equilibriums may emerge in the short run and the long run depending on various combinations of the parameters of the model. Our model predicts that in the short run equilibriums the levels of output supplied by the home (foreign) firm to the home country market are bigger (smaller) compared to the long-run equilibriums. Therefore, the first mover advantage should be gradually disappearing over time. In addition, our model suggests several empirically testable hypotheses concerning the behavior of total output and prices in the industry after trade and investment liberalization.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 91-112
Keywords: exporting; foreign direct investment; leader follower model; proximity-concentration trade off